ANALISIS PENERAPAN KRIPTOGRAFI SEBAGAI SOLUSI KEAMANAN INFORMASI PADA SISTEM INFORMASI PERENCANAAN DAN AKUNTABILITAS KINERJA LEMBAGA SANDI NEGARA - Rangga Aditya Sutopo (2014)
Whether we like it or not, information technology has become part of our daily lives, and no exception with the government. It became the focus of attention of Lembaga Sandi Negara as well to implement e-government in Information System Planning and Performance Accountability or SIPAK Lemsaneg. However, refer to a growing number of threats and vulnerabilities that may affect the confidentiality, integrity and availability of data, it require contemporary security techniques to protect information assets that exist in valuable e-government handlings. From this situation, the objective of the reseach is to determine the method or technique appropriate for the cryptographical security of e-government in SIPAK as information security solutions that protect data and information of SIPAK. In order to determine the appropriate cryptographic techniques, SIPAK require information security standards that serve as guidelines in determining the stages that is worth to be followed. One of such standard is the NIST SP 800-21 using SDLC as data analysis techniques. The metodology will be applied in this research as well. Results of the research showed that the SIPAK possesses some assets that turned out to have limited classifications requirements to be secured. From the data obtained it became obvious that vulnerabilities and threats can disrupt the te majority and scope of SIPAK and Lemsaneg. Based on the results, it is recommended to use cryptography with AES-128 encryption for database security, SHA-256 for password security and SSL / TLS 3.0 for network security